Advances in understanding vertebrate nephrogenesis. Issue 4 (1st October 2020) - Chambers, Joseph M.; Wingert, Rebecca A.
ABSTRACT: The kidney is a complex organ that performs essential functions such as blood filtration and fluid homeostasis, among others. Recent years have heralded significant advancements in our knowledge of the mechanisms that control kidney formation. Here, we provide an overview of vertebrate renal development with a focus on nephrogenesis, the process of generating the epithelialized functional units of the kidney. These steps begin with intermediate mesoderm specification and proceed all the way to the terminally differentiated nephron cell, with many detailed stages in between. The establishment of nephron architecture with proper cellular barriers is vital throughout these processes. Continuously striving to gain further insights into nephrogenesis can ultimately lead to a better understanding and potential treatments for developmental maladies such as Congenital Anomalies of the Kidney and Urinary Tract (CAKUT).